2021
DOI: 10.25105/dim.v18i1.8814
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Fungsi Ruang Dalam Pada Keraton Kacirebonan

Abstract: Keraton merupakan tempat tinggal bagi raja dan keluarganya pada bangunan diposisi sentral. Menurut Agustina (2013;2014) Keraton dalam pandangan kosmologis merupakan pusat kekuatan gaib yang berpengaruh pada seluruh kehidupan masyarakat.begitu pula dengan susunan keruangan keraton di Jawa mengadaptasi kepada susunan Gunung Mahameru, yaitu ada daerah puncak dengan anak gunungnya. Puncak Gunung adalah bangunan inti yang melambangkan gunung Mahameru. Hirarki ruang ditunjukkan dengan penaikkan lantai dimana ruang y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In Java, Santoso, Setioko and Pandelaki (2021) saw that there had been a change in the sacred space around the palace, namely the Kidul Square of the Surakarta Palace, which was influenced by changes in the physical condition and function of the square as a result of the development of the city's present and future needs. In another study, Royandi et al, (2021) showed a significant change in space's physical function and function. The nature and value of space are no longer essential as a sacred space due to tourism factors and economic factors' needs.…”
Section: 0mentioning
confidence: 92%
“…In Java, Santoso, Setioko and Pandelaki (2021) saw that there had been a change in the sacred space around the palace, namely the Kidul Square of the Surakarta Palace, which was influenced by changes in the physical condition and function of the square as a result of the development of the city's present and future needs. In another study, Royandi et al, (2021) showed a significant change in space's physical function and function. The nature and value of space are no longer essential as a sacred space due to tourism factors and economic factors' needs.…”
Section: 0mentioning
confidence: 92%
“…Sama halnya dengan kedua keraton di Cirebon, Keraton Kacirebonan juga memiliki tata letak bangunan memanjang dari utara ke selatan. Keraton Kacirebonan hanya memiliki satu akses gerbang masuk yang dikelilingi oleh benteng sebagai pembatas dengan permukiman warga [11].…”
Section: Gambar 3 Keraton Kacirebonan (Hasil Dokumentasi 2021)unclassified